Significant difference of serum 25-hydroxyvitamin D level in male hemodialysis patients with or without diabetes; a single center study - Nasri Hamid; Rafieian-Kopaei Mahmoud (Society of Diabetic Nephropathy Prevention, 2012)
It is well found that the assessment of circulating 25-hydroxyvitamin D offers better information about vitamin D status in patients. This cross-sectional study was aimed to better understand the probable difference of 25-hydroxyvitamin D level in a group of hemodialysis (HD) patients with or without diabetes. 25-hydroxyvitamin D level (normal range of values is 25 to 125 nmol/L) was measured following an overnight fasting. The study was conducted on 36 subjects (15 female, 21 male), consisting of 25 (female=11, male=14) non-diabetic HD patients and 11 (female=4, male=7) diabetic HD patients. A significant difference of serum 25-hydroxyvitamin D level between diabetic and non-diabetic male HD patients with more values of 25-hydroxyvitamin D level in none-diabetic HD patients was found (r=0.014). Least studied was conducted on the influence of diabetes on 25-hydroxyvitamin D level in HD patients, lower vitamin D level in diabetes patients may aggravates their condition. Thus, further investigations need to define this aspect of hemodialysis patients.